2017
DOI: 10.1530/joe-16-0368
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tissue culture in the presence of VEGF and fetuin stimulates follicle growth and steroidogenesis

Abstract: Ovarian tissue cryopreservation together with follicle culture provides a promising technique for fertility preservation in cancer patients. The study aimed to evaluate follicle parameters in a culture medium supplemented with VEGFA165 and/or fetuin. Vitrified-warmed ovarian cortical pieces were divided randomly into four culture groups consisting of basic culture medium (control), and the basic culture medium supplemented with VEGFA165, fetuin or both. After six days of culture, we evaluated the following: pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 73 publications
3
19
0
Order By: Relevance
“…30 Additionally, we found that fetuin-A downregulated tissue MDA, TNF-a, and IL-1b levels. Furthermore, our results were in line with those of Asadi et al 31 who noticed that fetuin enhanced total antioxidant capacity levels and also prevented the formation of MDA in ovarian tissue. These findings are in agreement with the observations of Sarı€ ozkan et al, 32 who indicated that supplementation of the medium used to freeze sperm with fetuin or a combination of fetuin and hyaluronan decreased ROS and MDA levels.…”
Section: Discussionsupporting
confidence: 93%
“…30 Additionally, we found that fetuin-A downregulated tissue MDA, TNF-a, and IL-1b levels. Furthermore, our results were in line with those of Asadi et al 31 who noticed that fetuin enhanced total antioxidant capacity levels and also prevented the formation of MDA in ovarian tissue. These findings are in agreement with the observations of Sarı€ ozkan et al, 32 who indicated that supplementation of the medium used to freeze sperm with fetuin or a combination of fetuin and hyaluronan decreased ROS and MDA levels.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of mRNA levels in cumulus cells is related to the oocyte maturity and fertilization rate ( 45 ), and the addition of GDF-9 or BMP-15 in IVC system can promote the activation of human primordial follicles, with seemingly more beneficial effects of GDF9 ( 46 ). Other factors, such as basic fibroblast growth factor (bFGF), kit ligand (KITL), keratinocyte growth factor (KGF), leukemia inhibitory factor (LIF), stem cell factor (SCF), vascular endothelial growth factor (VEGF), and cyclic adenosine monophosphate (cAMP), have also been proved to improve the activation and survival of cultured follicles in vitro ( 47 49 ). Shown in Table 1 .…”
Section: Initial Stage: In Vitro Activation (Iva) mentioning
confidence: 99%
“…Various growth factors have been shown to promote some activation of primordial follicles in humans (Abir et al 2006, Garor et al 2009, Kedem et al 2011b, Streiter et al 2016 including stem cell factor (Carlsson et al 2006a), insulin and insulin-like growth factors (Yuan & Giudice 1999, Louhio et al 2000, Stubbs et al 2013, basic fibroblast growth factor (Garor et al 2009, Wang et al 2014, growth and differentiating factor 9 (Hreinsson et al 2002, Kedem et al 2011b, bone morphogenetic factor 15 (Kedem et al 2011b) and VEGF165 with fetuin (Asadi et al 2017). However, development was limited to early secondary stages.…”
Section: In Vitro Culture Of Ovarian Folliclesmentioning
confidence: 99%